"It's about time": Twitter responses to gender change with Doctor Who's 13th Doctor. (2nd January 2023) - Grome, Rebekah; Drumheller, Kristina; Kinsky, Emily S.
ABSTRACT: Quantitative content analysis was used to examine social media responses to the BBC's announcement of the first female Doctor in the science-fiction show Doctor Who . Tweets reacting to the BBC's framing of the decision ( N = 2, 971) were coded for mentions of representation, impact on the character, political correctness, feminism, impact on ratings, and impact on younger generations. Results indicated that audience responses did not reflect the BBC's framing but were generally supportive of the casting choice. Explanations for the lack of correspondence between the BBC and responses are explored.